INSIDENSI SERANGAN HAMA PENGGEREK BATANG PADA PERSEMAIAN KALIANDRA DI PT.USAHA TANI LESTARI SUMBA BARAT NTT. - Wida Darwiati Jusuf; Mira Yulianti (Universitas Nusa Bangsa, 2020)
Stem borers at Kaliandra Nursery In PT Usaha Tani Lestari, Sumba Barat NTT. Pest attack is the major problem in the cultivation of energy-producing wood plants, one of which is a stem borer that attacks Kaliandra (Calliandra callothyrsus) plant. The information regarding the level of stem borer attack is needed as a material consideration in the management of the energy-producing timber plant. The purpose of this study is to assess the incidence, calculate the percentage and intensity of attacks and identify the stem borer. This research was conducted at Kaliandra Nursery PT. Sustainable Farming in West Sumba, NTT. The results showed that the identification of stem borer pests of the Xyleborus sp (Scolytidae: Coleoptera) species. 7-month-old seedlings have been attacked with an average stem diameter of 1.21 cm and a stem height of 63.7 cm. The holes produced by the pest Xyleborus sp by 2 mm with the highest number of hole holes 30 points per seed. the distance of the first drill hole from the base is 3.01 cm and the final distance of the drill hole is 56.96 cm. The results of the percentage of attacks reached 90% with the category of severe attacks, the incidence of stem borer pests are also driven by very extreme weather factors/heat.Keywords: Stem Borer, Kaliandra, Percentage, And Intensity of The AttackABSTRAK Serangan hama merupakan masalah utama yang dihadapi dalam budidaya tanaman penghasil kayu energi, salah satunya adalah hama penggerek batang yang banyak menyerang tanaman kaliandra (Calliandra callothyrsus). Informasi mengenai tingkat serangan hama penggerek batang diperlukan sebagai bahan pertimbangan dalam pengelolaan tanaman penghasil kayu energi tersebut. Tujuan penelitian ini adalah mengkaji insidensi, menghitung persentase dan intensitas serangan serta mengidentifikasi hama penggerek batang tersebut. Penelitian ini dilaksanakan di persemaian kaliandra PT. Usaha Tani Lestari Sumba Barat, NTT. Hasil penelitian menunjukkan bahwa identifikasi hama penggerek batang adalah dari jenis Xyleborus sp (Scolytidae : Coleoptera). Bibit umur 7 bulan sudah terserang dengan rata-rata diameter batang 1,21 cm dan tinggi batang 63,7 cm. Lubang gerek yang dihasilkan hama Xyleborus sp sebesar 2 mm dengan jumlah lubang gerek terbanyak 30 titik per bibit. Jarak lubang gerek pertama dari pangkal bawah 3,01 cm dan jarak terakhir lubang gerek sepanjang 56,96 cm. Hasil persentase serangan mencapai 90% dengan kategori serangan yang berat, insidensi hama penggerek batang tersebut juga dipacu oleh faktor cuaca yang sangat ekstrem /panas.Kata Kunci : Hama penggerek batang, kaliandra, persentase, dan intensitas serangan